Charisma in Education: A Cautionary Note (Journal of Education and Development, 2026)
This paper offers a review of the literature on the nature of charisma in the scholarship of teaching and learning(SoTL). This synthesis of the literature will reveal three salient themes that SoTL authors have used tounderstand the concept of charisma in teaching: namely, that charisma is an uncultivable rare ‗gift‘, thatcharisma involves the use of humor and that charisma is expressed by intense high energy rituals. It will beargued that all three themes are problematic for SoTL researchers and practitioners. It is hoped that findingsfrom this paper will prompt a reconceptualization of charisma in SoTL research as well as constitute someoptimism for teachers whose professional identities are portrayed as lacking charisma.